2021
DOI: 10.1021/acscatal.1c03169
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopically Guided Simulations Reveal Distinct Strategies for Positioning Substrates to Achieve Selectivity in Nonheme Fe(II)/α-Ketoglutarate-Dependent Halogenases

Abstract: Nonheme iron halogenases, such as SyrB2, WelO5, and BesD, halogenate unactivated carbon atoms of diverse substrates at ambient conditions with exquisite selectivity seldom matched by nonbiological catalysts. Using experimentally guided molecular dynamics (MD) simulations augmented with multiscale (i.e., quantum mechanics/molecular mechanics) simulations of substrate-bound complexes of BesD and WelO5, we investigate substrate/active-site dynamics that enable selective halogenation. Our simulations reveal that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 97 publications
2
58
0
Order By: Relevance
“…13 The prepared structure for WelO5 was obtained from ref. 29 . For all protein-substrate complexes, crystallizing agents were removed and missing residues were added using Modeller.…”
Section: A Protein Structure and Preparationmentioning
confidence: 99%
See 3 more Smart Citations
“…13 The prepared structure for WelO5 was obtained from ref. 29 . For all protein-substrate complexes, crystallizing agents were removed and missing residues were added using Modeller.…”
Section: A Protein Structure and Preparationmentioning
confidence: 99%
“…[22][23][24] Despite the intuitive role of the carboxylate substitution in halogenase reactivity, through the creation of a halide binding pocket, the re-introduction of a carboxylate through mutagenesis experiments does not confer native hydroxylase efficiency. 25 Further computational studies have revealed additional mechanisms that favor the challenging halogenation reaction over the thermodynamically preferred hydroxylation reaction such as direct positioning of the substrate, [26][27][28][29] active site isomerization, 30,31 inactivation of the hydroxyl ligand, 32,33 inherent reactivity of the rebound intermediate, 34,35 superior radical character on the halide, 36 and steric effects. 37 One of the most popular proposed mechanisms for selectivity control is the precise positioning of the substrate during halogenation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…36,63 The selectivity of rebound has been hypothesized to be derived from precise control over the substrate radical positioning relative to the two potential rebounding species to allow for the more difficult halogenation reaction to occur. [43][44][45][46]64,65 . Although pairs of Fe II /αKG-dependent amino acid hydroxylases with regio-divergent outcomes have been reported 62,[66][67][68] , it is remarkable that the two halogenases, BesD and HalB, overcome the additional challenging of precisely orienting lysine within the active site to achieve regioselectivity without compromising selectivity for halogenation over hydroxylation.…”
Section: Lysine-bound Crystal Structure Of Halbmentioning
confidence: 99%